Uji Efektivitas Perangkap Kuning Berperekat dan Atraktan terhadap Serangan Lalat Buah pada Pertanaman Jeruk di Desa Katung, Kecamatan Kintamani, Kabupaten Bangli - SASTONO, I WAYAN; WIJAYA, I NYOMAN; ADNYANA, I MADE MEGA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.4, Oktober 2017, 2017)
Study on Effectivity of Attractant and Yellow Sticky Trap Fruit Flies on Citrus Orchards in Katung Village, Kintamani District, Regency of Bangli The research was carried out in Katung Village, Kintamani district, of Bangli Regency from periode of May until October 2016. This research was conducted in order to compare the effectivity of trap using Methyl Eugenol (Petrogenol) and using a glue with the trade name is Leila. This research was used a relative method by taking 20 samples of citrus plant. The observation was done every week from the beginning of fruiting until harvesting. The trap using Methyl Eugenol (Petrogenol) was found more effective compare to trap using a glue (Leila).